Contribution of the Miguel Vega and Justo Prieto cases to the constitutional normative force in XXI century Mexico - Acosta Argüelles, Jorge Arturo (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
In this article, based on the concept of constitutional normative force, the cases of Miguel Vega and Justo Prieto that occurred in the 19th century are addressed, in which, for the first time, a diffuse control of constitutionality is carried out in Mexico. In this context, the contributions of these cases are analized in light of the two culminating points of the current Mexican constitutionalism, that is, as determined by the Supreme Court of Justice of the Nation, in the various file 912/2010 and in the contradiction of thesis 293/2011, on July 14, 2011 and on September 3, 2013, in terms of the constitutional reform on human rights, of June 2011.
Keywords: Constitutional normative force; democratic dualism; constitution; judicial review; Vega; Prieto